Getting Roped In: Group Cohesion, Trust, and Efficacy Following a Ropes Course Intervention. Issue 2 (July 2015) - Eatough, Erin; Chang, Chu‐Hsiang; Hall, Nicholas
<x xml:space="preserve">Abstract</x> The aim of this study was to explore the potential beneficial workgroup outcomes of a ropes course challenge intervention. Using three distinct samples (a military group, a medical facility workgroup, and a utility company workgroup), this study explored the systematic individual and group‐oriented outcomes achieved. Significant changes in group cohesion, group member trust, and group‐efficacy were found post‐ropes course intervention in all three samples. Two of the three samples additionally demonstrated improvement in employees' self‐efficacy. Sample 3 examined trait coping style and demonstrated that employee social support coping predicted degree of change in group cohesion, but in an unexpected direction. Taken together, results suggest experiencing a ropes course challenge may foster improvement in group member trust, group‐ and self‐efficacy, and group cohesion—especially for individuals who are unaccustomed to seeking social support under stress. The potential gains of ropes course challenge interventions for workgroups may have been previously underestimated.